2020
DOI: 10.1128/aem.00877-20
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for a Growth Zone for Deep-Subsurface Microbial Clades in Near-Surface Anoxic Sediments

Abstract: Global marine sediments harbor a large and highly diverse microbial biosphere, but the mechanism by which this biosphere is established during sediment burial is largely unknown. During burial in marine sediments, concentrations of easily-metabolized organic compounds and total microbial cell abundance decrease. However, it is unknown whether some microbial clades increase with depth. We show total population increases in 38 microbial families over 3 cm of sediment depth in the upper 7.5 cm of White Oak River … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
4
11
0
Order By: Relevance
“…We further investigated present day environmental drivers and main evolutionary forces shaping the composition of prokaryotic communities populating the seafloor. In addition to the longitudinal structuration of communities, we confirm a systematic vertical stratification also reported at different depth scales in previous studies (Durbin and Teske, 2011;Orcutt et al, 2011;Jochum et al, 2017;Petro et al, 2019;Lloyd et al, 2020). We took advantage of the longitudinal extent of our dataset to investigate what processes might be at play in the assembly of microbial communities in and just below the bioturbation zone.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We further investigated present day environmental drivers and main evolutionary forces shaping the composition of prokaryotic communities populating the seafloor. In addition to the longitudinal structuration of communities, we confirm a systematic vertical stratification also reported at different depth scales in previous studies (Durbin and Teske, 2011;Orcutt et al, 2011;Jochum et al, 2017;Petro et al, 2019;Lloyd et al, 2020). We took advantage of the longitudinal extent of our dataset to investigate what processes might be at play in the assembly of microbial communities in and just below the bioturbation zone.…”
Section: Discussionsupporting
confidence: 85%
“…When comparing three adjacent sites (<10 km apart), we found that site-specific ASVs only marginally contributed to the total community (<1.8%, Figure 5D), whereas horizon-specific biomarkers, considered here as proxies for environmental filtering, were predominant (36.9-45.6% of reads). This finding is in line with the hypothesis of a strong environmental influence raised in previous work (Petro et al, 2017(Petro et al, , 2019Starnawski et al, 2017;Kirkpatrick et al, 2019;Marshall et al, 2019;Lloyd et al, 2020), even within the first decimeters of sediment. The observations from Petro et al (2019) on the depth of influence of the bioturbation zone are also in line with the detection of macrofauna in a parallel metabarcoding study on these Mediterranean and Atlantic samples.…”
Section: Environmental Filtering and Ecological Drift In Subsurface Community Assemblysupporting
confidence: 93%
See 2 more Smart Citations
“…Due to the isolation from the surface, time scales for surface derived water or carbon can range from years to hundreds of millions of years (Lippmann et al, 2003;Lin et al, 2006;Holland et al, 2013). Thus, it stands to reason that deep microbial systems operate on time scales that are counter to what we observe in the lab or at the surface, i.e., growth rates in the lab range from minutes to weeks, while subsurface may see growth on the order of years to decades (Hoehler and Jørgensen, 2013;Xie et al, 2013;Onstott et al, 2014;Trembath-Reichert et al, 2017;Lloyd et al, 2020). As a whole, the subsurface is highly populated with microorganisms.…”
Section: Introductionmentioning
confidence: 98%